105k views
3 votes
10m-3(2m-9)=9(m-1)+1

User Hett
by
6.2k points

2 Answers

5 votes

Answer:

i think the answer is 137

i hope this helps you

i am sorry if this is wrong

:(




User Muhammad Naufil
by
5.8k points
2 votes

Answer:

m=7

Explanation:

10m -3(2m-9) = 9(m-1)+1

Distribute the -3 into 2m-9

10m-6m+27=9(m-1)+1

Now distribute the 9 into m-1

10m-6m+27=9m-9+1

Then we should be able to solve from there.

4m+27 =9m-8

+8 +8

4m+35=9m

-4m -4m

35= 5m

35/5 = 5m/5

7=m


So it is m = 7

User GuedesBF
by
6.0k points